The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1177/070674371405900802
|View full text |Cite
|
Sign up to set email alerts
|

Competent Psychopharmacology

Abstract: There is little doubt that undergraduate and post-graduate training of physicians, pharmacists, and nurses is insufficient to prepare them to use psychotropics safely and effectively, especially in the context of their expanded off-label uses. Therefore, the development of competencies in psychotropic prescribing needs to be approached as a long-term, practice-based learning commitment. Proposed are the abilities and knowledge components necessary for safe and effective use of psychotropics. Typical challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In addition to quality and safety, medication errors can have economic implications for the healthcare system. In the United Kingdom (UK), the Department of Health report states that preventable medication errors cost the NHS by as much as £2.5bn a year (Torjesen, 2014 (Gardner, 2014). Moreover, the explosion in neuro-scientific and psychological understanding of mental disorders have compounded the problem (Glick & Rush, 2016).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to quality and safety, medication errors can have economic implications for the healthcare system. In the United Kingdom (UK), the Department of Health report states that preventable medication errors cost the NHS by as much as £2.5bn a year (Torjesen, 2014 (Gardner, 2014). Moreover, the explosion in neuro-scientific and psychological understanding of mental disorders have compounded the problem (Glick & Rush, 2016).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…In support of this view, the results from our regression analysis showed that knowledge gained through experience accounted for only 4% of the variance, suggesting that 96% of the learning was through other means. Because of these limitations, proposals for improving the teaching of psychopharmacology have been discussed (Gardner, 2014;Jones et al, 2010;Skingsley et al, 2006) but the implementation of these strategies remains a significant challenge.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Few other subjects may be addressed, looking at the future. The teaching of specific areas of psychiatry, such as child and adolescent psychiatry 25 , competent psychopharmacology 26 , community psychiatry 27 or substance abuse 8 may need a more detailed analysis. We are particularly interested in the potential role of trainees as clinical teachers of medical students in psychiatry 28 ; and are also supportive of the need to try to homogenize the core curricula across medical schools 23 .…”
Section: Discussionmentioning
confidence: 99%
“…These roles are possible and supported by a trusting public who frequently access pharmacists’ services [ 9 – 11 ]. However, impediments have been described that serve to undermine the potential value of community pharmacists in building on their contributions to mental health and addictions care in their communities [ 12 19 ].…”
Section: Introductionmentioning
confidence: 99%